Analysis of saving' determinants among smallholders cash crop farmers: a case study of Polokwane Local Municipality in Limpopo Province, South Africa - Marutha, Morongwa Innocent (My University, 2021)
Smallholder cash crop farmers form part of the economy’s growth potential and savings are enormously important for stability within their farms. Farmers in South Africa have been faced with environmental catastrophes such as: droughts, floods, etc. These farmers require a backup for them to rise after these environmental disasters. This is where savings start to become more imperative for smallholder farmers. Regardless of how important savings are, South Africa has been characterized by low and declining savings from the household level and smallholder cash crop farmers typically generate income for consumption without saving. This study examined the savings’ determinants among smallholder cash crop farmers in Polokwane local municipality. A non-probability sampling technique called purposive sampling was used in this study and 70 smallholder cash crop farmers participated as respondents for this study. Descriptive statistics were used to describe the socio-economic characteristics of the smallholder cash crop farmers; the cash crops grown by these farmers and the constraints that militated against their savings. While the binary logistic regression model was employed to analyze the factors influencing savings of the smallholder cash crop farmers. The most preferred cash crops by the farmers in the study area are maize, potatoes, tomatoes, butternut, and groundnuts. The factors influencing the savings by these farmers are farm: income (p<0,050), household size (p<0,014) , farm size(p<0,045) , membership in a cooperative or association(p<0,018) and financial literacy(p<0,048).The major constraints that militated against savings by these farmers are: farm income, the cost of their labour, financial illiteracy and banking costs. It was discovered in this study that smallholder farmers’ savings ability, regardless of their intentions or willingness to save is highly dependent on their income and farming costs. Therefore, the study recommends that strategies to increase smallholder cash crop farmer’s income must be harnessed through provision of other income generating opportunities. Financial illiteracy adversely affects the smallholder cash crop farmers' ability to save, and it is also recommended that smallholder cash crop farmers should be provided with financial education
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2021
Keywords: Smallholder; Economy; Cash crop farmers; Farmers -- South Africa -- Limpopo; Economic development -- South Africa -- Limpopo; Cash crops; Farms, Small -- South Africa -- Limpopo